The Influence of Narcissism, Job Insecurity on Counterproductive Work Behavior with Negative Emotions as Mediator (Study on Generation Z Employees) - Tulak, Wasty; Siswanti, Yuni; Nurhariati, Emmy; Sudaryati, Sudaryati; Bantulu, Yusna (AIBPM Publisher, 2023)
This research was carried out at a company adapter, data cables, gaming headsets, earphones, headphones, mice, mouse pads, etc. The objective of this study is to examine the impact of job insecurity and narcissism on counterproductive work behavior with negative emotions as mediators. This study employs quantitative techniques that are derived from purposive sampling on Generation Z workers at Company X, located in Kaliurang, Yogyakarta, Indonesia. The number of respondents was 70 employees. Data collection was carried out using questionnaires and interviews. This research used statistical analysis with SEM (Structural Equation Modeling) with Smart PLS 4.0. The research results show that 1) Narcissism has a positive and significant effect on counterproductive work behavior, 2) Narcissism has a positive and significant effect on negative emotions, 3) Narcissism has a positive and significant effect on counterproductive work behavior mediated by negative emotions, 4) Job insecurity has a positive and significant effect on counterproductive work behavior significantly towards counterproductive work behavior, 5) Job insecurity has a positive and significant impact on negative emotions, 6) Job insecurity has a positive and significant impact on counterproductive work behavior mediated by negative emotions. Further research needs to be done related to other variables that affect CWB in the millennial generation.